What Methods are used for Statistical Reasoning Learning?: A Systematic Literature Review - Gunadi, Farid; Juandi, Dadang (FKIP Universitas Lampung, 2022)
A student’s statistical reasoning ability is needed as a good and precise foundation, so that a teacher is demanded to use the proper methods to improve students’ statistical reasoning. This research aims to know the appropriate methods used to improve students’ statistical reasoning ability and the methods' steps. Systematic Literature Review (SLR) is employed in three steps. The SLR stages are carried out in three stages, namely Planning the Review, Conducting the Review, Reporting and Disseminating. Article searching by using Harzing’s Publish or Perish Application and data analysis using atlas.ti with coding Histoorical Background, Context Solution, Research Questions or Objectives, Methodology, Conclusions, and Findings. The findings of statistical reasoning learning are Statistical Reasoning Learning Environment (SRLE), Experiential Learning, Blended Learning, 4MAT learning style system, and Brain-based Learning. From those methods, Statistical Reasoning Learning Environment is used primarily in the learning process. Keywords: statistical reasoning, systematic literature review, publish or perish. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp345-359